Minat Penggunaan M-Banking Bank Konvensional di Kabupaten Sumbawa: Implementasi Technology Acceptance Model - Firman, Firman; Nurjihadi, Muhammad (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2023)
This study aims to examine the public's interest in using m-banking in conventional banks in Sumbawa Regency. The Technology Acceptance Model (TAM) was employed as the underlying framework, and the research was conducted using a field survey method. Data for this study were collected online through convenience sampling using a self-registered questionnaire. The data were analyzed using Structural Equation Modeling (SEM) Partial Least Squares (PLS). The findings indicate significant influences between attitude toward using, perceived ease of use, perceived usefulness, and smartphone self efficacy on m-banking usage intention. Perceived ease of use, perceived usefulness, and user experience have a significant impact on m-banking usage intention. Additionally, smartphone self efficacy also influences the perceived ease of use in m-banking, but it does not have an effect on the perceived usefulness. These findings provide a better understanding of the factors influencing the public's interest in using m-banking in conventional banks in Sumbawa Regency.